"Plug and play" full-dimensional ab initio potential energy and dipole moment surfaces and anharmonic vibrational analysis for CH4–H2O. Issue 12 (28th March 2015) - Qu, Chen; Conte, Riccardo; Houston, Paul L.; Bowman, Joel M.
<x xml:space="preserve">Abstract</x> The first full-dimensional potential energy surface of CH4–H2O dimer is presented, and vibrational analysis of this dimer is performed.